Analisis Faktor-Faktor Yang Mempengaruhi Return Saham Dengan Profitabilitas Sebagai Variabel Intervening - Septin Dwi Rahmawati; Diana Dwi Astuti; Lia Rachmawati (STIE Mandala Jember, 2020)
Manufacturing companies are companies that produce raw goods into finished goods, one of which is the consumer goods industry. The consumer goods industry is an industry that society needs to produce products for daily needs. Therefore, investors continue to look at the shares of this industry because they are considered to be always stable in determining the level of profit production. The purpose of this study is to understand the factors that influence stock returns with profitability as an intervening variable. The data used are secondary data collected from the Indonesia Stock Exchange 2014-2018 publications. The data processing method uses the path analysis method with IBM SPSS version 22. The results of the study show that Earnings Per Share and Debt Adequacy Ratio are related to Profitability. Yield Dividend, Firm Size, and Growth does not affect Profitability. Growth concerns Stock Returns, but Company Size, Dividend Results, Firm Size and Profitability Adequacy Ratio can be intervening variables Earning Per Share, but Profitability is not able to become intervening variables such as Yield Dividend, Company Size, Growth and Debt Adequacy Ratio.